Developing a concession pricing model for PPP highway projects - Xu, Yelin; J. Skibniewski, Miroslaw; Zhang, Yongmei; P. C. Chan, Albert; F. Y. Yeung, John (International Journal of Strategic Property Management, 2012)
The concession pricing is one of the most important issues during the negotiation period of PPP contracts. Pricing should vary in accordance with risks assumed by the private sector and embody equitable risk sharing between the government and the private sector to lower the minimum feasible concession price and ensure effective risk management. In this study, a general concession pricing model is developed through cost-benefit analysis from the perspective of the private sector. The model integrates project risk variables, price parameters, and other financial elements into a concession pricing formula based on cash flow table. Meanwhile, to cope with the occurrence of unforeseeable losses triggered by risk factors, such as interest rate fluctuation, inflation, traffic volume change, etc., a price adjustment mechanism is established to adjust the initial price and ensure the project's financial viability. The concession pricing model and adjustment mechanism allow the government and the private sector to reach a consensus on the tariff scheme of a PPP project. It is believed that the model is beneficial to create a “win-win” situation for both the government and the private sector.First Publish Online: 19 Jun 2012